PERBANDINGAN SISTEM PEMILIHAN UMUM PRESIDEN AMERIKA SERIKAT DENGAN INDONESIA - Doris Febriyanti; M. Jerry Pratama (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
This Research is based on of curiosity researchers know how indonesia (in the era of order reform ) and the united states as a country with system of government presidensial , in this case president and vice president. Both countries had a different way in elect president and his deputy where indonesia elect president and vice president directly while united states has a president and his deputy with a system of electoral college / represented through the electoral vote.The purpose of this research is to find and analyze the comparison about the system of presidential election between United States Of America and Indonesia.Keywords : Election, United states, Indonesia, Comparison